2016
DOI: 10.3389/fgene.2016.00153
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Pathological Aging Affects Chromatin Dynamics, Structure and Function at the Nuclear Edge

Abstract: Lamins are intermediate filaments that form a complex meshwork at the inner nuclear membrane. Mammalian cells express two types of Lamins, Lamins A/C and Lamins B, encoded by three different genes, LMNA, LMNB1, and LMNB2. Mutations in the LMNA gene are associated with a group of phenotypically diverse diseases referred to as laminopathies. Lamins interact with a large number of binding partners including proteins of the nuclear envelope but also chromatin-associated factors. Lamins not only constitute a scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 205 publications
(279 reference statements)
0
22
0
1
Order By: Relevance
“…Detailed reviews of these laminopathies can be found elsewhere, e.g. (Robin and Magdinier, 2016). Interestingly, loss of the peripheral heterochromatin layer has been observed by electron microscopy in cells from patients with autosomal recessive mandibuloacral dysplasia (Filesi et al, 2005) or Hutchinson–Gilford Progeria Syndrome (Shumaker et al, 2006), which are both caused by mutations in Lamin A.…”
Section: Outlook and Future Challengesmentioning
confidence: 99%
“…Detailed reviews of these laminopathies can be found elsewhere, e.g. (Robin and Magdinier, 2016). Interestingly, loss of the peripheral heterochromatin layer has been observed by electron microscopy in cells from patients with autosomal recessive mandibuloacral dysplasia (Filesi et al, 2005) or Hutchinson–Gilford Progeria Syndrome (Shumaker et al, 2006), which are both caused by mutations in Lamin A.…”
Section: Outlook and Future Challengesmentioning
confidence: 99%
“…The H3K9me3 chromatin‐enriched domains, like pericentrosome region or telomeres, are not SAHF components but are located at their periphery (Narita et al, 2003; Zhang et al, 2005, 2007). Additional heterochromatin components together with HP1 and H3K9me3 contribute to heterochromatin remodeling, namely MacroH2A (histone variant related to gene silencing), histone cell cycle defective homolog A (HIRA), and anti‐silencing function 1A (Robin & Magdinier, 2016).…”
Section: Chromatin Organizationmentioning
confidence: 99%
“…At the cellular level, lamins A and C form filaments that are mainly present at the nuclear periphery but are also observed in the nucleoplasm ( 3 ). Laminopathies are characterized by nuclear morphological abnormalities and an altered pattern of heterochromatin distribution that is more severe in progeroid syndromes, including Hutchinson-Gilford progeria syndrome (HGPS), mandibuloacral dysplasia (MAD), atypical-Werner syndrome (WS) and restrictive dermopathy (RD) ( 4 , 5 ). The lamin filament network interacts with chromatin at different stages of the cell cycle: in ana-telophase, lamin A and C dimers are recruited at the core regions of sister chromosomes; in interphase cells, they relocalize both at the nuclear envelope and within the nucleoplasm, where lamins A and C provide anchor points for chromatin ( 6–9 ).…”
Section: Introductionmentioning
confidence: 99%